Improving the Experience of Controlling Avatars in Camera-Based Games Using Physical Input - Li, Na; Moraveji, Neema; Kimura, Hiroaki; Ofek, Eyal (The 14th ACM International Conference on Multimedia, Santa Barbara, CA, USA 2006, 2006)
This paper investigates two methods of improving the user experience of camera-based interaction. First, problems that arise when avatars are designed to mimic a user’s physical actions are presented. Second, a solution is proposed: adding a layer of separation between user and avatar while retaining intuitive user control. Two methods are proposed for this separation: spatially and temporally. Implementations of these methods are then presented in the context of a simple game and evaluate their effect on performance and satisfaction. Results of a human subject experiment are presented, showing that reducing the amount of user control can maintain, and even improve, user satisfaction if the design of such a reduction is appropriate. This is followed by a discussion of how the findings inform camera-based game design.